Regional experience in organizing the protection of minors from a destructive information environment (by the example of non-central regions) - S. E. Titor (Вестник университета, 2023)
Achievements in the field of new technologies, on which the formation of the modern information society is based, have led to the rapid development of the global computer network Internet. The Internet as a means of social communication has both a positive impact on the world community and has negative consequences. The relevance of protecting minors from destructive information is quite high, since in the modern world, where technology has taken a leading position in human life, including children. Researchers believe that a comprehensive solution to the problem of ensuring the information security of minors is impossible without coordinated actions of federal and regional authorities. The following regions were selected for the study: the Republic of Buryatia, Irkutsk Region, Khanty-Mansiysk District, Yamalo-Nenets District. This was not done by chance, since these regions have their own specifics: the first and main ones are located geographically far from the center of Russia, from the capital Moscow. They have their own special climatic and economic features. In terms of their territorial size, these regions are many times larger than the average regions in the central part of Russia. This specificity determines the relevance of the study of these regions. The study analyzes the legislative framework of the regions regulating the protection of minors from negative information, as well as law enforcement practice.